Development of e-LKPD Based on Real Problems in Theory Statistics Data Class VI SDN 101868 Sena Village - Wijaya, Nadia Oktia Putri; Hidayat, Hidayat (Universitas Trunojoyo Madura, 2022)
This research is motivated by the absence of appropriate teaching materials in the online learning process. Learning is only done through whatsapp groups because of the limited distance between teachers and students. This study aims to produce Electronic Student Worksheets (e-LKPD) based on Real Problems on data statistics material with sub-materials mean, median and mode to be applied in mathematics learning activities in elementary school and determine the feasibility of the developed e-LKPD. The subjects in this study were material experts and media experts. This type of research is research and development ( RD ) using ADDIE Analysis (Analysis), Design (Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). However, this research only limits the stages to the ADD stage, namely Analysis, Design, and Development. The instrument used in this study was a validation sheet that was reviewed by material experts and media experts. The data analysis technique used in this study is a qualitative descriptive analysis technique. The results of this study are e-LKPD products based on Real Problems that fall into the